AN INTRUCTIONAL DESIGN FOR THE TEACHING OF ENGLISH AT SMP MUHAMMADIYAH I KARTASURA 2013 ACADEMIC YEAR: A NATURALISTIC STUDY - Dian Muhammad Rifai (Universitas Muhammadiyah Surakarta, 2013)
This study is aimed at analyzing the instructional desgin for the teaching of English at SMP Muhammadiyah I Kartasura 2013 academic year. In this research, there are nine components of instructional design investigated, namely: (1) learning objective, (2) syllabus, (3) roles of instructional material, (4) classroom procedure, (5) classroom technique, (6) teacher’s role, (7) learner’s role, (8) media, and (9) evaluation model. The type of the study is descriptive qualitative especially naturalistic approach. In this research, the data are devired from event, informant, and field note. There are three techniques of collecting data, namely: observation, interview, and document. The techniques of analyzing data are collecting data, data reduction, data display, and verification conclusion. The result of the study, such as: (1) The general objective is to deveop students’ individual knowledge, character, skill for independent life and sustainable education. The specific learning objective is to develop students’ communicative competence with four language skills: listening, speaking, reading, and writing; (2) The type of syllabus is notion functional syllabus; (3) the roles of instructional materials are as a resource for presentation materials, for learner practice, and for stimulation of classroom activities; (4) the classroom procedure used are Engagement, Exploration, Explanation, Elaboration and Evaluation and Genre Based Approach; (5) the teacher’s role are facilitator, organizer, manager, assessor, planner and motivator; (6) the media used in teaching learning process is used textbook and picture as printed media, video and images showed by using LCD.